PENGARUH BEBAN KERJA PRAKTIKUM DAN MOTIVASI TERHADAP KINERJA MAHASISWA DALAM BERKOMPETISI PADA NILAI AKADEMIK - Andriana, Iyan; Rinaldy, Aldi Muhammad (Inaque : Journal of Industrial and Quality Engineering, 2019)
This research is to explain the effect of practical work load and motivation on student performance. The phenomenon has one weight of sks practical each semester identic for three hours courses, this issue is different than the other courses. Path analysis could explain how big student performance was impacted by practical work load and motivation. Path analysis is a development technique from multiple regression which using for testing variables in research object on each path. The input is how the practical work load has a relationship with motivation is positive and significant which in value is 0.32. This research has three results; first, there is an effect of practical work load and motivation on student performance. Second, has an impact between practical work load with student performance. Third, the result is explain an effect of motivation on student performance. Each indicator’s values are 50.03%, 16.98%, and 33.05%. Based on the results and using significant level 5% explaining the more amount of practical work load, then influence the student motivation and otherwise, this research confirms that practical work load and motivation has an significant effect on student performance.